Cinética de fotodegradação natural de contaminantes emergentes em ETE aeróbia - Moraes, Gustavo Henrique (Universidade Federal de São Carlos, 2019)
The advances in sample preparation and analytical detection techniques made possible the evaluation of a new class of contaminants found in the ug L-1 – ng L-1 range, known as Emerging Contaminants (EC). Along with that, the changes in the consumption patterns made their occurrence more frequent in the aquatic environment, where pharmaceuticals and personal care produtcs (PPCP), a class of the EC, have been continuously detected, since the wastewater treatment plants (WWTP) were not projected to remove these molecules. The unitery operations involved on the sewage treatment in aerobic WWTP are sometimes carried out under open sky, making the photodegradation with natural sunlight of PPCPs possible. Thus, this study has as the main goal the evaluation of the behaviour of 8 pharmaceuticals and 1 personal care product regarding their photodegradation with natural sunlight in sewage and in ultrapure water. Five photodegradation assays were performed with both matrices fortified with the analytes, as well as a monitoring of such molecules in an aerobic WWTP for 24 h. Out of the nine molecules studied, atenolol and caffeine did not suffer any photolysis. Carbamazepine showed some photodegradation only in the assay with the solar exposure that was less interrupted by clouds. However, its half-life times were as high as 85,4 and 105,8 h, respectively in sewage and in ultrapure water. Naproxen was the most susceptible molecule to suffer photodegradation both in sewage and in ultrapure water, showing half-life times on the range 5,6 – 9,9 h for the former and about half of it for the latter matrix, indicating that the sewage can act as a competitor on the absorbance of solar radiation by the compound. The second most susceptible analyte both in sewage and in ultrapure water was diclofenac, with t1/2 between 5,6 and 21,8 h for the former and between 4,5 and 11,1 h for the latter. Such data indicate that for diclofenac, the same attenuation effect observed for naproxen was present. Ibuprofen showed low photodegradation, specially in sewage, as expected, since this molecule does not absorb light within the solar radiation spectrum region that reaches the terrestrial surface (290 to 800 nm). Acetaminophen presented low degradation in ultrapure water, process interfered by the sewage matrix. Propranolol and triclosan were photolabile only in sewage, demonstrating that the indirect photodegradation can have an important function on the attenuation of their concentrations. By monitoring the studied WWTP, it was possible to notice that even the most photolabile contaminants determined throughout the photodegradation assays were not degraded on the real scenario of the aerobic WWTP. Therefore, it can be concluded that six out of the nine compounds studied suffered natural photodegradation, but the configurations involved on the treatment of the sewage do not offer the right conditions for the photolytic processes to occur.
Natural photodegradation kinetics of emerging contaminants in an aerobic WWTP
Keywords: Fotodegradação; Fármacos e produtos de higiene pessoal; Esgoto; Photodegradation; Pharmaceuticals and personal care products; Wastewater; CIENCIAS EXATAS E DA TERRA::QUIMICA